Neuroprotective effects of saikosaponin-A in ethanol-induced glia-mediated neuroinflammation, oxidative stress via RAGE/TLR4/NFkB signaling - Ali, Waqar; Choe, Kyonghwan; Kang, Min Hwa; Ali, Jawad; Park, Hyun Young; Atiq, Abubakar; Ahmad, Sareer; Park, Tae Ju; Kim, Myeong Ok (Frontiers in Cellular Neuroscience, 2025)
Chronic use of ethanol leads to psychological and physiological dependence followed by neurodegeneration via glia-mediated neuroinflammation, and oxidative stress. The current study is aimed at the neuroprotective effects of saikosaponin-A against ethanol-induced neurodegeneration. Here, saikosaponin-A 10 mg/kg i.p., for 7 days was used against the ethanol (5 g/kg i.p., for 6 weeks) induced neuroinflammation via RAGE/TLR4 signaling in mouse neurodegenerative model. The immunoblotting and immunofluorescences microscopy results showed that, ethanol activates the glial cells at the level of mice brain. The relative expression of Toll like receptor (TLR4), receptor for advance glycation end product (RAGE), ionized calcium binding adaptor molecules 1 (Iba-1), glial fibrillary acidic protein (GFAP) was upregulated in ethanol-treated mice group. However, expression level of inflammatory biomarkers were downregulated in ethanol + SSA co-treated group. Similarly, our finding revealed that SSA significantly reduced the protein expression level of Phospo c-Jun N-Terminal Kinase (p-JNK), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) and downstream signaling targets in ethanol + SSA co-treated group. SSA also regulates the elevated ethanol-induced oxidative stress via NRF2 and HO-1 proteins. Finally, we analyzed the synaptic and behavioral alteration that was reversed in SSA treated group. Taken together, we concluded that SSA exhibits anti-inflammatory and antioxidant effects against ethanol-induced neurodegeneration.